The effect of N-acetylcysteine and working memory training on glutamate concentrations in the dACC and rACC in regular cocaine users – A randomized proof of concept study. (25th September 2021) - Schulte, Mieke H.J.; Goudriaan, Anna E.; Boendermaker, Wouter J.; van den Brink, Wim; Wiers, Reinout W.
Highlights: High relapse rates stress the need for effective cocaine use disorder treatments. Baseline glutamate concentrations did not correlate with cocaine use or impulsivity. No effect of NAC on brain Glx concentrations detected in 9 regular cocaine users. No effect of WM training on brain Glx concentrations detected in 9 regular cocaine users. Future research needs to improve adherence of working memory training. Abstract: Introduction: Current treatments for cocaine use disorder (CUD) are not very effective and better treatments are needed. This study investigates the effectiveness of a combined intervention that targets the assumed underlying glutamate pathology in cocaine users. To this end, the combined effects of N-acetylcysteine (NAC) and working memory (WM) training on glutamate concentrations in the dorsal and rostral ACC were investigated in a randomized, double-blind placebo-controlled design. Methods: In this study, 38 regular cocaine-using men were randomized to either 25-days with 2400 mg/day NAC and WM-training or 25 days with placebo with WM-training. Cocaine use, impulsivity, and glutamate concentrations in the dACC and rACC using proton Magnetic Resonance Spectroscopy were assessed at baseline and after treatment. Results: Twenty-four participants completed the study, of which 9 received NAC and 15 received placebo. There were no baseline correlations of glutamate concentrations in the dACC or rACC with cocaine use measures or impulsivity. Additionally, there were no effects of NAC, WM-training, or the combination thereof on (changes in) glutamate concentrations in the dACC or rACC. Discussion: This randomized proof of concept study could not confirm our hypotheses. Possible explanations are insufficient power and the possible absence of deviant baseline glutamate concentrations in the included participants. Future studies should consider larger samples and a non-using control group to confirm baseline deviations in glutamate in cocaine users.